2015
DOI: 10.1007/s11547-015-0496-2
|View full text |Cite
|
Sign up to set email alerts
|

Metal and motion artifacts by cone beam computed tomography (CBCT) in dental and maxillofacial study

Abstract: In our series Cone-Beam-CT diagnostic evaluation was never inhibited by metal artifacts and only in 1.9% of the cases by motion artifacts, always with a very low CT-dose-index.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
69
0
6

Year Published

2016
2016
2024
2024

Publication Types

Select...
3
3
1

Relationship

1
6

Authors

Journals

citations
Cited by 74 publications
(78 citation statements)
references
References 35 publications
3
69
0
6
Order By: Relevance
“…In fact, approximately 21-42% of the in vivo examinations exhibit motion artefacts. 2,3 Recently, several works have been published in the literature about movements in dental and maxillofacial CBCT, [2][3][4][5][6][7][8][9][10] but correlation between the various possible movements and the resulting different kinds of artefacts, which may be induced, is lacking.…”
Section: Introductionmentioning
confidence: 99%
“…In fact, approximately 21-42% of the in vivo examinations exhibit motion artefacts. 2,3 Recently, several works have been published in the literature about movements in dental and maxillofacial CBCT, [2][3][4][5][6][7][8][9][10] but correlation between the various possible movements and the resulting different kinds of artefacts, which may be induced, is lacking.…”
Section: Introductionmentioning
confidence: 99%
“…12 It is well known that patient motion artefacts influence the obtainable resolution of the final CBCT reconstructed image, rather than the resolution of the unit's flat panel detector. 12 Very few studies 13,14,16 in the literature have assessed the image quality and visual characteristics of CBCT examination for the presence of artefacts supposedly related to patient movement. These studies reported that between 4.5% and 41.5% of CBCT examinations show artefacts suggestive of patient movement.…”
Section: Discussionmentioning
confidence: 99%
“…These studies reported that between 4.5% and 41.5% of CBCT examinations show artefacts suggestive of patient movement. 13,14,16 But, although some studies 7,8 report on the possible impact of motion artefacts on image quality, knowledge of which types and magnitudes of movements may considerably hamper the diagnostic outcome of a CBCT examination is still a key question. 8 Moreover, it is unclear whether observed artefacts in some studies 13,14,16 were in fact due to patient motion.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations